The Influence Of Return On Assets (Roa), Return On Equity (Roe), And Gross Profit Margin (Gpm) On Stock Prices With Earnings Per Share (Eps) As A Moderating Variable (An Empirical Study On Food And Beverage Sub-Sector Companies Listed On The Indonesia Stock Exchange For The Period 2017–2024) - Tanuraharja, Shanty; Samosir, David Kiki Baringin MT (AKUNTOTEKNOLOGI : JURNAL ILMIAH AKUNTANSI DAN TEKNOLOGI, 2025)
Financial performance is a key indicator used by investors to assess a company’s prospects and value. Ratios such as Return on Assets (ROA), Return on Equity (ROE), and Gross Profit Margin (GPM) provide insights into how efficiently a company manages its assets, capital, and ability to generate profit. Changes in these financial indicators often influence stock price movements, making them important factors in investment decision-making. However, the relationship between financial performance and stock prices is not always consistent. Other factors, including macroeconomic conditions and the distribution of profits to shareholders, may strengthen or weaken this relationship. Earnings Per Share (EPS) is one such variable that can moderate the effect of financial performance on stock prices, as it reflects the portion of earnings received by each shareholder and serves as one of the most widely used indicators in company valuation. The food and beverage sector is known for its relative stability but experienced significant pressure during the 2017–2024 period, especially due to the Covid-19 pandemic. Shifts in consumer behavior, demand fluctuations, and supply chain disruptions created volatility in financial performance, which in turn affected stock prices. These conditions make the sector relevant for further empirical investigation. To produce measurable and objective findings, this study employs a quantitative research approach using statistical tools, including classical assumption tests and multiple linear regression analysis. These statistical methods ensure that the influence of ROA, ROE, and GPM on stock prices, as well as the moderating role of EPS, can be examined empirically and supported by valid analytical evidence.